Amazon S3 cookbook : over 30 hands-on recipes that will get you up and running with Amazon Simple Storage Service (S3) efficiently - Hashimoto, Naoya (Quick answers to common problems., 2015)
Over 30 hands-on recipes that will get you up and running with Amazon Simple Storage Service (S3) efficiently About This Book Learn how to store, manage, and access your data with AWS SDKs Study the Amazon S3 pricing model and learn how to calculate costs by simulating practical scenarios Optimize your Amazon S3 bucket by following step-by-step instructions of how to deliver your content with CloudFront, secure the S3 bucket with IAM, and lower costs with object life cycle management Who This Book Is For This book is for cloud developers who have experience of using Amazon S3 and are also familiar with Amazon S3. What You Will Learn Host a static website on Amazon S3 Calculate costs with AWS Simple Monthly Calculators Deploy a static website via CloudFormation Distribute your content via CloudFront Secure resources with bucket policies and IAM Protect objects using server-side and client-side encryption Enable Cross-Origin Resource Sharing Manage objects' life cycles to lower costs Optimize performance for uploading as well as downloading objects Enable S3 event notifications and create Lambda functions Manage common operations with AWS SDKs In Detail Amazon S3 is one of the most famous and trailblazing cloud object storage services, which is highly scalable, low-latency, and economical. Users only pay for what they use and can store and retrieve any amount of data at any time over the Internet, which attracts Hadoop users who run clusters on EC2. The book starts by showing you how to install several AWS SDKs such as iOS, Java, Node.js, PHP, Python, and Ruby and shows you how to manage objects. Then, you'll be taught how to use the installed AWS SDKs to develop applications with Amazon S3. Furthermore, you will explore the Amazon S3 pricing model and will learn how to annotate S3 billing with cost allocation tagging. In addition to this, the book covers several practical recipes about how to distribute your content with CloudFront, secure your content with IAM, optimize Amazon S3 performance, and notify S3 events with Lambada. By the end of this book, you will be successfully implementing pro-level practices, techniques, and solutions in Amazon S3. Style and approach A step-by-step practical guide that will show you how to efficiently store, manage, and control your data in Amazon S3.